The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1158/1535-7163.mct-08-0264
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive imaging of cell proliferation following mitogenic extracellular kinase inhibition by PD0325901

Abstract: The mitogenic extracellular kinase 1/2 (MEK1/2) inhibitor, PD0325901, has potent activity in a number of cancer cell types in vitro. In SKMEL-28 human melanoma cells (BRAF mutant), the drug rapidly decreased phosphorylated extracellular signal-regulated kinase 1/2, cyclin D1, and thymidine kinase 1 protein levels. We investigated if 3 ¶-deoxy-3 ¶-[ 18

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…This observation is supported by a past study showing that a oral administration of PD0325901 was shown to suppress tumor growth by inhibition of ERK1/2 activation in HT116 (KRAS mutation) xenograft. 25 These results indicate that decreased ERK1/2 phosphorylation plays an important role in the inhibition of oxaliplatin-induced neuropathy and tumor growth by PD0325901.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This observation is supported by a past study showing that a oral administration of PD0325901 was shown to suppress tumor growth by inhibition of ERK1/2 activation in HT116 (KRAS mutation) xenograft. 25 These results indicate that decreased ERK1/2 phosphorylation plays an important role in the inhibition of oxaliplatin-induced neuropathy and tumor growth by PD0325901.…”
Section: Discussionmentioning
confidence: 76%
“…The mice were maintained in a pathogen-free environment at 25 C under controlled lighting (12-hr light/12-hr dark cycle) and allowed free access to water and food pellets.…”
Section: Micementioning
confidence: 99%
“…5B). This indicates that D4-FCH can be used to detect treatment response even under conditions where large changes in tumor size reduction are not seen (31). To understand the biomarker changes, we examined the intrinsic cellular effect of PD0325901 on D4-FCH-phosphocholine formation by treating exponentially growing HCT116 cells in culture with PD0325901 for 24 h and measuring the 60 min uptake of D4-FCH in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Both tumor-bearing (BALB/c nude mice) and non-tumor-bearing (BALB/c mice) animals were used. Human melanoma, SKMEL-28, and human colon, HCT116, tumors were grown in BALB/c nu/nu mice (Harlan) as reported previously (31). Tumor dimensions were measured continuously using a caliper and tumor volumes were calculated by the equation: volume = (p / 6)  a  b  c, where a, b, and c represent three orthogonal axes of the tumor.…”
Section: Radiopharmaceuticalsmentioning
confidence: 99%
“…Similarly, Shapiro et al reported that PMR was attained in 6 of 15 (40%) evaluable patients treated with a combination of the MEK inhibitor GDC-0973 and the PI3K inhibitor GDC-0941 in a dose-escalation trial (22). 18 F-fluoro-39-deoxy-39-L-fluorothymidine PET to investigate inhibition of proliferation by the MEK inhibitor PD0325901 has also been investigated (23,24). Although several other studies have confirmed the utility of PET in clinical trials, to our knowledge, this was the first study for which 18 F-FDG PET was used in a systematic and consistent manner over 2 phase I clinical trials with a view to comparing 2 compounds with similar mechanisms of action and guiding the most appropriate dose schedule to take forward into phase II.…”
Section: Discussionmentioning
confidence: 99%